Representations of women and men in popular chemistry textbooks in the United Kingdom and Republic of Ireland. Issue 2 (23rd December 2021) - Murray, Claire; Anderson, Yvonne; Simms, Charlie H.; Seery, Michael K.
Abstract : Textbooks are an important aspect of students' school lives and the representation of scientists in textbooks is a proxy for the representation of who can do science. This study investigated the names of scientists and other people mentioned in four commonly used textbooks in the three education systems in the UK and Republic of Ireland (England, Wales, and Northern Ireland using the A Level system; Scotland using the Curriculum for Excellence Highers system; Republic of Ireland using the Leaving Certificate system) and characterised them by gender. We found an overwhelming bias towards naming of famous men in three of the four textbooks (1 man and 0 women in the A Level textbook; 8 men and 0 women in the first, and 48 men and 2 women in the second Curriculum for Excellence textbooks, and 45 men and 1 woman in the Leaving Certificate). We subsequently analysed images and again found a dominance of images representing men in three of the four textbooks including only 4 women in a total of 68 images in the Leaving Certificate textbook. These images were analysed by role (scientist or not), and by activity according to UNESCO criteria. There was a tendency to show men in scientific and other occupational roles while women were less well represented in scientific roles and were pictured in domestic and buying activities. This work aims to raise awareness of these representations and prompt action for reform in line with UN Strategic Development goals.